Globalization and the Media - Nyiam, Davina (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
The subject of globalization is widely discussed and debated by scholars and scientists all over the world. The academic community has also given serious thought to the impact of globalization on media management across the globe. The relationship between globalization and media has been subjected to serious communication evaluations to sensitize the policy makers, professionals, academicians, researchers and other stakeholders on their role and responsibility. A review of the relevant literature suggests that the impact of globalization on media management and operations is not adequately examined by the researchers to date. An attempt is made in this work to evaluate the impact of globalization on media management. It was also felt necessary to identify and analyze the disadvantages of globalization on media management in order to suggest suitable preventive, protective and promotional measures that would enhance the status, credibility and efficiency of media institutions in Nigeria.